Study of the electrochemical reduction of amoebicide Teclozan and its amperometric determination in pharmaceutical formulations - Santos, Andri L.; Takeuchi, Regina M. [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Esteves, Ana Paula; Medeiros, Maria Jose (Soc Brasileira Quimica, 2008)
The electrochemical reduction of amoebicide Teclozan (TEC) was studied on a glassy carbon electrode in acetonitrile. Controlled-potential electrolyses were performed for coulometric and preparative purposes. The electrogenerated products were isolated by liquid-liquid extraction and characterized by (1)H NMR. It was observed that TEC presents two voltammetric peaks, each one associated with the cleavage of two C-Cl bonds. In presence of a proton donor it was observed that the first peak at -1.8 V promotes mainly the reduction of the groups CHCl(2) to CH(2)Cl and the second one at -2.2 V promotes the reduction of the groups CH(2)Cl to CH(3) giving as the sole product the completely dechlorinated TEC derivative with yields between 82 and 97%. In addition, a comparative study between the analytical performance of voltammetric techniques and amperometric detection of TEC in hydrodynamic conditions was performed. The amperometric detection was more sensitive than all evaluated voltammetric techniques, providing a detection limit of 8.9 x 10(-6) mol L(-1).
Keywords: amperometric detection; glassy carbon electrode; chloroacetamides; Teclozan